2018
DOI: 10.22161/ijaers.5.12.35
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pesticides handling Practices and Health and Environmental Impacts on Khat Growing Farmers: in Haro Maya Woreda, Eastern Ethiopia

Abstract: Methods were designed to evaluate the handling practice and the effect of pesticides on environment and human health. The data were collected by participating mainly Khat growing farmers and further supported by interviewing health and agricultural professionals, field observation and focal group discussion with Khat chewers. 97.1 % of farmers used pesticides for pest control. The survey revealed that, 95.2% confirmed that they using DDT. The pesticide treated khat is harvested and consumed starting from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Pilot study participants (retailers and consumers) confirmed that pesticide chemicals are sprayed on Khat bushes and trees, and Khat farmers disclosed the use of Dichlorodiphenyltrichloroethane (DDT) and Malathion on their farm (Beyene et al, 2020). Another survey study in Haromaya Wereda also identified that the farmers were using pesticides including DDT for growing Khat (Regassa and Regassa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pilot study participants (retailers and consumers) confirmed that pesticide chemicals are sprayed on Khat bushes and trees, and Khat farmers disclosed the use of Dichlorodiphenyltrichloroethane (DDT) and Malathion on their farm (Beyene et al, 2020). Another survey study in Haromaya Wereda also identified that the farmers were using pesticides including DDT for growing Khat (Regassa and Regassa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was calculated using the single population formula. The total sample size was calculated to be 612 premised on a prevalence of 63% reported work-induced dermatoses in Khat farmers, 16 a margin of error ( d ) of 4%, a 95% confidence level of confidence, and a 10% non-response rate. Three hundred forty-seven farm laborers from the 16 large-scale farms were disqualified based on the eligibility criteria, giving a sample population to draw from 1298 employees.…”
Section: Methodsmentioning
confidence: 99%
“… 6 , 16 Contact dermatitis, an irritating, inflammatory skin reaction to foreign materials, is one of the most prevalent occupational-related disorders among Khat farm workers, and because occupational dermatitis commonly affects the hands, low-wage employees may lose their ability to work and earn an income. 16 , 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted on Khat expansion in Wondogenet, Southcentral Ethiopia, found that Khat growing farmers use different types of toxic pesticides as an insect controller and they spray it about 1-2 times per week on Khat [ 1 ]. Similarly, studies conducted on the status of pesticides in other parts of Ethiopia also evidenced the use of toxic pesticides for Khat growing purposes [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%